LAVISH WEDDING AMONG MUSLIMS IN NORTHERN NIGERIA - Abdullahi Muhammad Maigari (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2023)
Spending huge amount of money during wedding ceremony among Hausa and Fulani ethnic groups who are predominantly Muslims in Northern Nigeria is a new phenomenon. There is a change in the trend at which potential husband and wife spend ostentatiously at pre and post wedding events to impress the friends, relatives and the general public. The study adopted a Theory of Conspicuous consumption by Thorsten Veblen to explain the behaviour of some bride and groom in spending money to impress others. Methodologically, qualitative data were elicited from ten IDI with some newly wedded couples in Kano and Katsina metropolises. The study found that in an attempt to demonstrate one’s social and economic class in the society, some people spend money uncontrollably during their wedding or that of their children or relatives. The result further showed that the essence of the wedding spending is not to impress the couples but it is targeted at the audience, spectators or guests at the wedding which contravenes the teachings of Islam which admonish Muslims to be modest in all their social interactions and activities. The paper concluded that spending huge amount of money during wedding deter young people from getting married which leads to delay marriage among people of child bearing age in Kano and Katsina. This is rampant because the neglect of the Sunnah of Prophet Muhammad (Peace and Benediction of Allah be upon him) in wedding rites.